The seventh most important thing - Pearsall, Shelley (New York : Alfred A. Knopf, 2015)
"In 1963, thirteen-year-old Arthur is sentenced to community service helping the neighborhood Junk Man after he throws a brick at the old man's head in a moment of rage, but the junk he collects might be more important than he suspects. Inspired by the work of American folk artist James Hampton"--
Keywords: Hampton, James, -- 1909-1964 -- Juvenile fiction; Artists -- Juvenile fiction; African Americans -- Juvenile fiction; Community service (Punishment) -- Juvenile fiction; Hampton, James, -- 1909-1964 -- Fiction; Artists -- Fiction; Folk art -- Fiction; African Americans -- Fiction; Community service (Punishment) -- Fiction